Learners’ use of L1 in high school EFL reading lessons / Farideh Yaghobian - Farideh , Yaghobian (2017)
This study investigates learners’ use of L1 during EFL reading lessons in an Iranian high school located in Malaysia. Learners’ use of the first language (L1) in a second language (L2) classroom is a long standing, controversial issue, and has been researched extensively. Previous studies have called for more research to be conducted on L2 reading in a naturalistic social setting of a classroom. This study uses Lantolf’s Sociocultural Theory of L2 (SCT-L2) as a framework to investigate how learners use Persian (L1) to mediate their English reading in a social setting of a classroom context. Both a qualitative and quantitative analyses were performed. The study involved the participation of eleven Grade Nine and fifteen Grade 12 learners. Main sources of data include: (a) audio-recordings from classroom interactions, (b) transcripts of classroom interactions, and (c) follow-up interviews with learners. It was found that in both grade levels, learners used L1 to perform actively in the classroom. Learners’ L1 served them a variety of functions, both in their social and their private speech. It was also found that learners’ use of L1 varied according to the task they were performing. Grade 9 learners used their L1 actively and in a much higher proportion in their New Words Task, and for the widest range of functions, while the same held true for Grade 12 learners with their Reading Task. L1 brought about more engagement with the mentioned tasks and played a positive role in learners’ cognitive processes. It was also seen that learners used L1 in different ways to aid them. L1 was found to be more supportive for some learners, due to the way they utilized it. In some instances, L1 acted as a tool to provide help and to create a comfortable social context for the learners. It also helped in aiding their memory and in organizing their thinking, acted as a tool for comprehension, and acted as a tool to link old and new information, among other things. Instances of unsuccessful L1 mediation were also found and possible reasons are discussed. Implications for theory and for L2 pedagogy are discussed.